2014
DOI: 10.12968/jowc.2014.23.8.410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SertaSil on wound healing in the rat

Abstract: The study found that SertaSil reduced the time to reaching a clean wound by 60% compared to Gentaxane and promoted faster wound closure and better recovery. These findings suggest that SertaSil may be valuable for use in the treatment of wounds in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…This disarmament of both offensive and defensive weaponry returns control to the immune system. This was confirmed in a preclinical wound healing model (24), where MPPT, compared to the topical antibiotic gentamicin, led to a 107% (2.1fold) increase in the overall number of immune cells in the wound, including a 24.8-fold increase in the number of macrophages and a 7.2-fold increase in lymphocytes (23,24). The level of immune cells in the gentamicin group was similar to untreated controls.…”
Section: Introductionmentioning
confidence: 78%
“…This disarmament of both offensive and defensive weaponry returns control to the immune system. This was confirmed in a preclinical wound healing model (24), where MPPT, compared to the topical antibiotic gentamicin, led to a 107% (2.1fold) increase in the overall number of immune cells in the wound, including a 24.8-fold increase in the number of macrophages and a 7.2-fold increase in lymphocytes (23,24). The level of immune cells in the gentamicin group was similar to untreated controls.…”
Section: Introductionmentioning
confidence: 78%
“…Attention was payed to the standardization of wounds received, the size of which did not exceed 400 mm2. After 4-5 days, necrotomy of the affected area was performed and then treatment of wounds was begun until healing [2].Our previous studies found that rapid wound healing of various etiologies using melaninin occurred in the initial phase of the regeneration of the skin. Herein, analysis of active contraction of the wound surface in dynamics was evident on days 3, 5, 7, 9, 14, 21 and on the 30 th day.…”
Section: Matherials and Methodsmentioning
confidence: 99%
“…Розмір ран не пови-нен перевищувати 400 мм 2 . На 4-5-ту добу здійснювали некротомію уражених ділянок і починали лікування ран до повного загоєння [16]. Для визначення відсотка вологи у тка-нині зразки шкіри зважували на аналітичних вагах і висушували до постійної маси при 80°С у сушильній шафі СНОЛ 3,5.3.5.3.5./И1 (Росія).…”
Section: методикаunclassified